Preparation and Performance of Nano HMX/TNT Cocrystals. Issue 5 (20th May 2015) - Li, Hequn; An, Chongwei; Guo, Wenjian; Geng, Xiaoheng; Wang, Jingyu; Xu, Wenzheng
Abstract Cocrystals of 1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetraazacyclooctane (HMX) and 2, 4, 6‐trinitrotoluene (TNT) with high energy and low sensitivity were obtained by a spray drying method. Scanning electron microscopy (SEM), X‐ray diffraction (XRD), and Fourier Transform Raman spectroscopy (FT‐Raman) were used to characterize the raw materials and cocrystals. Impact sensitivity and thermal decomposition properties of the cocrystals were tested and analyzed. The results show that microparticles prepared by the spray drying method are spherical in shape and 1–10 μm in size. The particles are aggregates of many tiny cocrystals, ranging from 50 nm to 200 nm. The formation of cocrystals originates from the NO⋅⋅⋅H hydrogen bonding between NO2 (HMX) and CH3 (TNT). Compared with raw HMX, the impact sensitivity of the cocrystals reduces obviously and it is much harder to decompose the cocrystal thermally.